Averting biodiversity collapse in tropical forest protected areas - Laurance, William F.; Carolina Useche, D.; Rendeiro, Julio; Kalka, Margareta B.; Bradshaw, Corey J.A.; Sloan, Sean P.; Laurance, Susan G.W.; Campbell, Mason J.; Abernethy, Katharine A.; Alvarez, Patricia; Arroyo-Rodríguez, Víctor; Ashton, Peter Shaw; et al. (Nature, 2012)
The rapid disruption of tropical forests probably imperils global biodiversity more than any other contemporary phenomenon. With deforestation advancing quickly, protected areas are increasingly becoming final refuges for threatened species and natural ecosystem processes. However, many protected areas in the tropics are themselves vulnerable to human encroachment and other environmental stresses. As pressures mount, it is vital to know whether existing reserves can sustain their biodiversity. A critical constraint in addressing this question has been that data describing a broad array of biodiversity groups have been unavailable for a sufficiently large and representative sample of reserves. Here we present a uniquely comprehensive data set on changes over the past 20 to 30 years in 31 functional groups of species and 21 potential drivers of environmental change, for 60 protected areas stratified across the worlds major tropical regions. Our analysis reveals great variation in reserve health: about half of all reserves have been effective or performed passably, but the rest are experiencing an erosion of biodiversity that is often alarmingly widespread taxonomically and functionally. Habitat disruption, hunting and forest-product exploitation were the strongest predictors of declining reserve health. Crucially, environmental changes immediately outside reserves seemed nearly as important as those inside in determining their ecological fate, with changes inside reserves strongly mirroring those occurring around them. These findings suggest that tropical protected areas are often intimately linked ecologically to their surrounding habitats, and that a failure to stem broad-scale loss and degradation of such habitats could sharply increase the likelihood of serious biodiversity declines. © 2012 Macmillan Publishers Limited. All rights reserved.
Keywords: Anthropogenic Effect; Biodiversity; Data Set; Deforestation; Ecosystem Health; Endangered Species; Environmental Change; Environmental Degradation; Environmental Factor; Environmental Stress; Functional Group; Habitat Management; Protected Area; Refuge; Tropical Forest; Vulnerability; Animals Hunting; Biodiversity; Environmental Change; Environmental Exploitation; Habitat; Priority Journal; Tropical Rain Forest; Agriculture; Animal; Biodiversity; Conservation Of Natural Resources; Data Collection; Ecology; Endangered Species; Environmental Pollution; Fires; Forestry; Interviews As Topic; Mining; Population Growth; Questionnaires; Rain; Reproducibility Of Results; Research Personnel; Temperature; Trees; Tropical Climate